DEVELOPING COMMUNICATIVE SKILLS IN THE MEDICAL CONTEXT OF ENGLISH LANGUAGE COURSES FOR MEDICAL UNIVERSITIES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In the context of increasing globalization and the internationalization of healthcare systems, English has emerged as the dominant medium of professional communication in medicine. Consequently, the development of communicative competence in English has become a critical component of medical education. However, in many non-English-speaking contexts, English instruction for medical students remains predominantly form-focused, emphasizing grammar and translation rather than communicative functionality. This misalignment results in graduates who possess theoretical linguistic knowledge but lack the ability to effectively engage in professional medical discourse. The present study investigates pedagogical strategies for enhancing communicative competence among medical students within English for Specific Purposes (ESP) frameworks. Drawing upon contemporary approaches such as Communicative Language Teaching (CLT), Content and Language Integrated Learning (CLIL), and Task-Based Language Teaching (TBLT), the research adopts a quasi-experimental design involving control and experimental groups. The intervention incorporates authentic medical scenarios, simulation-based learning, and technology-enhanced instruction through platforms such as Kahoot and Gimkit. Quantitative data derived from pre- and post-intervention assessments, alongside qualitative data from classroom observations and learner feedback, reveal statistically significant improvements in the experimental group’s communicative performance. These include enhanced fluency, increased lexical range in medical discourse, improved pragmatic competence, and greater confidence in clinical communication contexts. The findings underscore the efficacy of integrating communicative, content-driven, and technology-mediated pedagogies in medical English instruction.